The involutive automorphisms of τ-compact operators affiliated with a type I von Neuman algebra - Kudaybergenov, K. K.; Kalandarov, T. S. (Methods of Functional Analysis and Topology, 2008)
Let M be a type I von Neumann algebra with a center Z, and a faithful normal semi-finite trace τ. Consider the algebra L(M, τ) of all τ-measurable operators with respect to M and let S_0(M, τ) be the subalgebra of τ-compact operators in L(M, τ). We prove that any Z-linear involutive automorphisms of S_0(M, τ) is inner.